Redução de desperdícios de materiais na construção civil: o caso das construtoras que possuem obras distantes da sede da empresa no nordeste do Brasil - Santos, Marcos Aurélio Araújo (Universidade do Vale do Rio dos Sinos, 2021)
The waste of materials has being indicated as one of the mais causes of the cnstruction costs increasing. The thesis investigates as alternative mitigating actions or the practice applications of the Lean Construction can contribute to reduce the waste of materials. The case study investigates fourteen builders from Northeast of Brazil. The results contribute indicating that the waste of materials in construction sites from the Building it is originated in the project and also in the fragility about the identification of suppliers. This deficiency causes na excessive acquisition of materials or the replacement of materials already used by others in reason the non similarity of these materials. To lead with this problem, the results help indicating that professionals already understand the necessity to implantate new Technologies and tactics. However, the results indicate the businessperson resistance in invest on projects. This counterpoint has led professionals to invest n courses with no companies incentive Where They work fr. The results show the attention to problem with providers for distant constructions from the head offices of the companies. To lead with this problem, companies need to identify providers in closest cities to have its demands attended in a system called Just in Time. Therefore, the clusters formation appear as an altenative to minimize stocks and wasting reduction.
Keywords: Construção enxuta; Desperdício de materiais; Construtoras; Fornecedores; Projetos; Tecnologias; Processos; Lean construction; Waste of materials; Builders; Providers; Projects; Technologies; Tactics; ACCNPQ::Engenharias::Engenharia de Produção